Estudos de improvisação ao vibrafone a partir de gravações do pianista Amilton Godoy: transcrições, adaptações e análises. - Carlos Henrique Fernandes (2021)
In recent years, has been possible to notice an increase in the use of the vibraphone in works associated with MPIB (Instrumental Popular Brazilian Music) as well as in research projects related to the use of the instrument in this context. This paper is in line with these studies, focusing on the study of improvisation on the vibraphone within the context of Brazilian Popular Music. The study proposed here is based on learning through listening, transcription, analysis and performance of solos by instrumentalists who are references within MPIB and, in the specific case of this work, the 'samba jazz' idiom. As we did not identify a vibraphonist in Brazil who has maintained a long and consolidated career in this genre, we chose pianist Amilton Godoy, from the Zimbo Trio group, as a basis of study. In this work we include a brief biography of Amilton who is, admittedly, one of the most influential pianists and musicians within the MPIB and ‘samba jazz’ scene. In order to identify elements of his improvisation style, we transcribed 10 solos which he recorded between 1965 and 2019. Through analysis of the solos, we were able to identify patterns and recurrent musical ideas characteristic of his performance. The solos and patterns were adapted for the vibraphone and used as a basis for the development of exercises for improvisation on the instrument within the language of samba jazz. Finally, we used the musical material from these exercises to write a vibraphone solo based on the theme of The Girl from Ipanema.